On the Use of the Geoid in Geophysics: A Case Study over the North-west Shelf of Australia - Featherstone, Will (CSIRO Publishing, 1997)
The geoid is the fundamental surface that defines the figure of the Earth. It is approximated by mean sea-level and undulates due to spatial variations in the Earth's gravity field. The use of the geoid in regional geophysics is illustrated for the North-West Shelf of Australia by removing long-wavelength geoid features, due predominantly to deep-Earth mass anomalies, in order to reveal near-surface structure. After this process, the residual geoid anomalies correlate well with known geological structures. Therefore, the geoid can provide information, complementary to other geophysical data, of the Earth's internal structure.